Arsitektur Bisnis pada Perusahaan Katering - Achmad Yusni Muzakky; Moch. Minanur Rahman; Muhammad Ainul Yaqin (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
In the modern business world, catering companies face significant challenges in managing complex operations such as order management, inventory, production, and delivery. Many catering companies struggle to align their business processes with the evolving needs of consumers, leading to inefficient resource utilization and declining service quality. This study aims to identify the key components and interactions among components in a business architecture based on The Open Group Architecture Framework (TOGAF). The research method employs the Architecture Development Method (ADM) approach from TOGAF, involving stages of requirements analysis and conceptual business architecture design. Research data were obtained through observations of ERP systems used by catering companies, covering order management, inventory management, production, delivery, procurement, and finance. The results reveal the identification of components and their interactions that support operational process integration and enhance resource efficiency. These findings are expected to serve as a foundation for developing a more integrated, strategic, and adaptive business architecture to support the sustainability of catering companies.